Citric avid and phosphorus on development and nutritional status of coffee seedling - Lemos, Vinícius Teixeira; França, André Cabral; Silva, Enilson de Barros; Marinho, Renan Luís da Silva; Franco, Miguel Henrique Rosa; Avellar, Moisés de; Freitas, Ana Flávia de; Reis, Lílian Alves de Carvalho; Corrêa, Juliano Miari; Carvalho, Gladyston Rodrigues (Coffee Science - ISSN 1984-3909, 2015)
In weathered soils, there is an increased retention of anions such as phosphate. Organic acids of low molecular mass have been shown an effective way to provide nutrients before it showed unavailable in the soil, such as phosphorus. The objective was to evaluate the quality and growth content of seedlings of ‘Catuaí Vermelho’ coffee (IAC-99), submitted the application of citric acid and phosphorus concentrations in the substrate. Was used the factorial scheme (4x4), being the first factor concerning the application of citric acid anidre to the substrate (0,0; 0,5; 1,0 e 2,0 mg dm-3), and the second concerning the doses of phosphorus (0, 450, 900 e 1800 mg P2O5 dm-3), in substrate. The experimental design was a randomized complete block with five replicates. The seeds were germinated in bags with standard substrate for coffee seedlings, adjusted according to the treatment with applications of phosphorus. Citric acid was applied when the seedlings had the cotyledons. The evaluation has been held at 180 days after sowing when the seedlings had four to five leaf pairs expands. Were measured the foliar levels, and fhytotechnical atributes and from these determined Dickson quality index. Doses of 1404.0 mg P2O5 dm-3 and 1.0 mg dm-3 of citric acid in the substrate positively influenced the maximum quality of the seedlings. Was not effective dose of 2.0 mg dm-3of citric acid for the development of the same quality to the point of planting, while increasing the concentration of Ca, N, P, S, Cu, Fe and Zn in the leaves.